2015
DOI: 10.3168/jds.2015-9672
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting expression of estrus measured by activity monitors and conception risk of lactating dairy cows

Abstract: The objective of this study was to determine risk-factors affecting increase in physical activity during estrus and pregnancy per artificial insemination (P/AI) in lactating dairy cows. Cows were monitored continuously by 2 automated activity monitors [a collar-mounted accelerometer (HT; Heatime, SCR Engineers, Netanya, Israel) and a leg-mounted pedometer (BO; Boumatic Heat-seeker-TX, Boumatic Dairy Equipment, Madison, WI)]. When an increase in activity was detected, body condition score (BCS) and blood sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
128
5
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(162 citation statements)
references
References 40 publications
(57 reference statements)
25
128
5
4
Order By: Relevance
“…Duration of activity episodes varied between 11 and 19.1 h (Table 1). Thereby, multiparous cows expressed lower intensity (Reith et al, 2014a) and peak activity (Madureira et al, 2015) as previously shown by López-Gatius et al (2005) who calculated that each additional lactation number caused a 21.4% decrease in locomotion. Negative effects of high milk production on activity were reported by Yániz et al (2006) and López-Gatius et al (2005) who observed a 20048.7 ± 0.6 (SE) HeatWatch Free-stall barn/concrete flooring Roelofs et al (2005) 11.8 10.0…”
Section: Secondary Signs Of Estrussupporting
confidence: 67%
See 3 more Smart Citations
“…Duration of activity episodes varied between 11 and 19.1 h (Table 1). Thereby, multiparous cows expressed lower intensity (Reith et al, 2014a) and peak activity (Madureira et al, 2015) as previously shown by López-Gatius et al (2005) who calculated that each additional lactation number caused a 21.4% decrease in locomotion. Negative effects of high milk production on activity were reported by Yániz et al (2006) and López-Gatius et al (2005) who observed a 20048.7 ± 0.6 (SE) HeatWatch Free-stall barn/concrete flooring Roelofs et al (2005) 11.8 10.0…”
Section: Secondary Signs Of Estrussupporting
confidence: 67%
“…Body reserves are mobilized to compensate for NEB and contribute to higher loss of BW and body condition score (BCS) (Liefers et al, 2003) which in turn affects fertility by fewer cows showing initiated estrus. In a recent study conducted by Madureira et al (2015) the BCS of an estrual cow affected significantly peak activity, as animals with BCS ⩽ 2.5 expressed less intense estrus patterns. In addition, NEB has been related to delayed resumption of ovarian activity, prolonged postpartum anestrus (Liefers et al, 2003), a greater incidence of irregular cycles (Wathes et al, 2007), decreased conception rates and increased pregnancy loss (Wiltbank et al, 2006).…”
Section: Pedometer Visual Observation (30 Min Every 3 H)mentioning
confidence: 94%
See 2 more Smart Citations
“…The comparable results of the increased locomotion activity of Holstein dairy cows in the estrus period in comparison with the reference period before estrus were detected also by our research (32.2 %). Significantly higher differences in the locomotion activity, when comparing the period before estrus with the values of this indicator in the estrus period, expressed by the level of the locomotion activity in the interval of two hours (u/2h), were recorded by Favero (1984) and Silper et al (2015) at the level of (77.3 u/2h), or Madureira et al (2013) who detected the average cows´ activity in the estrus period at the level of 72.8 u/2h. Fundamentally different results, based on their experiments, are stated by Firk et al (2002) who did not confirm the significant growth of the cows´ locomotion activity in the estrus period.…”
Section: Resultsmentioning
confidence: 95%